Burden of acute infections (except respiratory and diarrheal) and its risk factors among under-five children in India: A systematic review and meta-analysis - Ganguly, Enakshi; Sharma, Pawan K; Bunker, Clareann H (Indian Journal of Child Health, 2016)
Context: Acute infections of eyes, ears, skin, and others are a common cause of morbidity in under-five children. The overall burden of other infections and their risk factors is not known. Evidence Acquisition: Available literature was searched comprehensively using PubMed for acute infections (except acute respiratory and diarrheal diseases) using the relevant medical subject heading terms. Extracted articles were independently reviewed against inclusion/exclusion criteria and rated for quality. 10 articles were abstracted and reviewed to identify the reported prevalence and risk factors for acute infections among children. Results: The pooled prevalence of infections (not including acute respiratory and diarrhea) between 2002 and 2013 was 18.42 (95% confidence interval: 9.30-30.62), with reported range of 3.7-50.8%. The significantly positively associated factors reported in single studies were young age of the child, malnutrition, poor breastfeeding, low socio-economic status, animal rearing near household and mothers’ illiteracy for independent morbidities. Conclusion: The evidence on risk factors including breastfeeding, vaccination, age, and sex that predispose under-fiveIndian children to different infections is inconclusive. There is a need to conduct more studies on acute infections other than acute respiratory and diarrhea, to establish their determinants in Indian children.